Similarities of clinical practice guidelines in the management of lower pain: Literature review - Kaminski, Josilene de Souza da Conceição; de Carvalho, Aline dos Santos Moreira; Mendonça, Paloma Martins (Seven Editora, 2024)
Introduction: Clinical practice guidelines aim to assist reasoning and clinical decision-making, improve the effectiveness and efficiency of health care and standardize conduct, including care for patients with low back pain. Considering that evidence-based practice is necessary and that healthcare decisions integrate scientific evidence, knowledge and early adherence by healthcare professionals to clinical practice guidelines can accelerate recovery and reduce costs associated with low back pain. There is no informational material that is easy to read and interpret that encompasses the similarities of important national and international guidelines in the management of low back pain. Objective: To unify the similarities in the practice guidelines of low back pain clinics, involving diagnosis and request for imaging exams, to later prepare informative material for health professionals on this topic. Methods: This is a literature review, with a bibliographic survey carried out in electronic databases: National Library of Medicine (Medicine–PubMed), Medical Literature Analysis and Retrieval System (Medline), Latin American and Caribbean Literature in Health Sciences (Lilacs), Scientific Electronic Library Online (SciELO) and Google Scholar. Results: Ten guidelines were part of this study. Recommendations for taking anamnesis and physical examination were found in all guidelines. Diagnostic screening aims to identify patients with specific conditions as the cause of low back pain, in addition to the possibility of the presence of red and yellow flags. All guidelines discussed recommend that imaging should be avoided unless there is clinical suspicion of red flag pathology, or severe or progressive neurological deficit, such as radiculopathy, neurogenic claudication, or if imaging is likely to guide additional management. Conclusion: Clinical practice guidelines for low back pain present well-established similarities in the management of low back pain. Most have common information regarding anamnesis, physical and neurological examinations and request for imaging exams. All guidelines in this study agree that imaging exams should be avoided. The preparation of the informative material will be presented in a future article, which will assist health professionals in better managing low back pain. DOI:https://doi.org/10.56238/sevened2024.016-025